Integration of activating and inhibitory receptor signaling by regulated phosphorylation of Vav1 in immune cells - Mesecke, Sven; Urlaub, Doris; Busch, Hauke; Eils, Roland; Watzl, Carsten (Science signaling, 2011)
Natural killer (NK) cells are effector cells of the immune system whose activation is carefully regulated by the interplay of signals from activating and inhibitory receptors. Signals from activating receptors induce phosphorylation of the guanine nucleotide exchange factor Vav1, whereas those from inhibitory receptors lead to the dephosphorylation of Vav1 by the Src homology 2 domain–containing protein tyrosine phosphatase 1 (SHP-1). Here, we used mathematical modeling and experiments with NK cells to gain insight into this integration of positive and negative signals at a molecular level. Our data showed a switch-like regulation of Vav1 phosphorylation, the extent of which correlated with the cytotoxic activity of NK cells. Comparison of our experimental results with the predictions that we derived from an ensemble of 72 mathematical models showed that a physical association between Src family kinases and activating receptors on NK cells was essential to generate the cytotoxic response. Our data support a central role for Vav1 in determining the cytotoxic activity of NK cells and provide insight into the molecular mechanism of the integration of positive and negative signals during lymphocyte activation.